18F FDG PET-CT in Evaluation of Prostate Cancer – Experience at NINMAS - Mutsuddy, Pupree; Dinu, Shahnaj Hossain; Mandal, Tapati; Akter, Papia; Kar, Rashmi; Rahman, S M Arifur; Siddique, Md Abu Bakker; Begum, Fatima; Sultana, Sadia; Begum, Shamim M F (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Fluorine-18 Fluorodeoxyglucose positron emission tomography-computed tomography (18F FDG PET-CT) is the most widely used oncologic imaging tool. However, due to some limitations and with the advent of newer disease-specific tracers 18F FDG is not routinely recommended in prostate cancer. However, in a developing country like Bangladesh with a growing cancer burden and where 18F FDG is an available tracer, we have tried to describe our experience in detecting the extent of disease in PCa. Methods: Retrospectively reviewed data of 18F FDG PET-CT of total 25 prostate cancer patients referred to National Institute of Nuclear Medicine and Allied Sciences (NINMAS) from February, 2021 to August, 2023 were included. Each patient’s PET-CT findings were reviewed in relation with histologic grade, Gleason’s score and serum PSA level. Results: Among the 25 patients with two patients came for baseline scan. 23 patients came for follow up evaluation with mean time for follow up from diagnosis being 26.8 months and all of them received treatment according to stage and standard guideline. In thirteen patients (52%) 18F FDG PET scan was negative with mean PSA 4.2 ng/ml and most of them (85%) were in grade group 2 and 3 with low Gleason’s score (6 to 7). 18F FDG PET was positive in 12 patients (48%) including the two patients who came for baseline staging with mean PSA 145.46 ng/ml. Those two patients had isolated focal hypermetabolic lesion in prostate. Rest of the 10 patients with positive PET scan found high serum PSA level (mean PSA 167.67 ng/ml) with Gleason’s score 8 to 10 and histologically all patients had poorly differentiated adenocarcinoma. Conclusion: 18F FDG PET-CT can detect presence of disease in prostate cancer in follow up cases with raised PSA level and with high grade group or Gleason’s score at the time of diagnosis. 18F FDG PET-CT can be a valuable tool for diagnosis of recurrence/metastases and follow up of prostate cancer in a cost-effective way in a developing country like Bangladesh. 18F FDG PET-CT effectively detects prostate cancer in high-grade cases, providing a cost-effective method for recurrence and metastatic diagnosis in developing countries like Bangladesh. Bangladesh J. Nuclear Med. 28(1): 55-61, 2025